2020
DOI: 10.1111/jan.14294
|View full text |Cite
|
Sign up to set email alerts
|

Rebuilding and guiding a care community: A grounded theory of end‐of‐life nursing care practice in long‐term care settings

Abstract: Aims To investigate the end‐of‐life (EOL) nursing care practice process in long‐term care (LTC) settings for older adults in Japan. Design A qualitative study based on grounded theory developed by Corbin and Strauss. Methods Sampling, interviewing, and analysis were performed cyclically, with results for each stage used as the basis for data collection and next‐stage analysis decisions. Semi‐structured interviews were conducted from March 2015‐March 2019 with 22 nurses from eight LTC settings. Analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…25 This study confirmed that RNs need to know nutritional recommendations for older people and pay attention to their patients’ eating behaviors; 41 for example, a patient who is not eating or drinking may have a certain restriction or not like the food. Our findings support earlier studies that pointed out that gerontological RNs need to be familiar with palliative 42 and end-of-life care, 43 having diverse competencies in different levels of palliative care. 44 RNs should also have experience with various pain relief methods, 25 treatment of other symptoms, the provision of psychosocial support and how to face a patient’s family when they are grieving.…”
Section: Discussionsupporting
confidence: 91%
“…25 This study confirmed that RNs need to know nutritional recommendations for older people and pay attention to their patients’ eating behaviors; 41 for example, a patient who is not eating or drinking may have a certain restriction or not like the food. Our findings support earlier studies that pointed out that gerontological RNs need to be familiar with palliative 42 and end-of-life care, 43 having diverse competencies in different levels of palliative care. 44 RNs should also have experience with various pain relief methods, 25 treatment of other symptoms, the provision of psychosocial support and how to face a patient’s family when they are grieving.…”
Section: Discussionsupporting
confidence: 91%
“…In Japan, men tend to continue living at home using home care services, even at a highly dependent level of daily living, while women tend to live in facilities (Tamiya, 2008). It is possible that more men who are cared for at home may have more ED visits than women who live in facilities where they receive adequate primary and palliative care (Nasu et al, 2020). However, this study had no data on the location where PwD were receiving care at the time of the ED visits.…”
Section: Discussionmentioning
confidence: 99%
“…This study adopted a qualitative descriptive design (Sandelowski, 2000), in conjunction with a qualitative study of EOL nursing care practice in LTC settings for older adults. The content on EOL nursing care has already been published (Nasu, Sato, et al, 2020). We report the analysis results of the interview data on a good death for PwD in LTC settings, which were not analysed or detailed in the first paper.…”
Section: Methodsmentioning
confidence: 99%